INFORMATION ON THE BIOLOGY OF THE BUTTERFLY (LEPIDOPTERA, SPHINGIDAE) MACROGLOSSUM STELLATARUM (LINNAEUS, 1758) IN THE CONDITIONS OF SOUTH FERGANA (Scientific journal of the Fergana State University, 2023)
The article is devoted to the distribution and biology of the butterfly Macroglossum stellatarum (Linnaeus, 1758). As a result of the research, data on biology, distribution and morphological description of Macroglossum stellatarum in the southern territories of the Ferghana Valley are given.